Free Movement of EU Citizens and Their Family Members. Issue 2 (June 2016) - Guild, Elspeth
Why is there so much friction between EU citizens moving in the European Union and state authorities regarding the third country national family members of those citizens? What are the fears of state authorities and what are the objectives of mobile EU citizens regarding their family members? This article examines these questions from an interrogation of the case law of the Court of Justice of the European Union. It investigates the sources of disaccord or inadequate articulation between what EU citizens want and what state authorities seek to control.